Amplitude-frequency characteristics of the seat vibration protection system with a three-segment static force characteristic with a section of quasi-zero stiffness - Korytov M.S.; Sherbakov V.S.; Kashapova I.E. (Научно-технический вестник Брянского государственного университета)
Vibration protection for heavy equipment operators is important. Exposure to vibration is harmful to health. Vibration protection seats are used for protection. Reliable passive systems with quasi-zero stiffness are promising. For the developed design of the seat on the basis of parallelogram mechanism, spring, cable and rollers, the study of vibration-protective properties is carried out. The design scheme has been developed, key parameters have been selected, and their study on vibration protection parameters has been carried out. The static force response was approximated by three linear segments with a horizontal mean. The known dynamic model describing forced oscillations of the mass was used. The displacement of the base was given by a harmonic function. Vibration protection systems with three-segment and with one-segment static force response were compared. The comparison was carried out in terms of transmission coefficients, accelerations and suspension displacement. The results of the computational experiment are presented in the form of graphs: amplitude-frequency characteristics in the form of transmission coefficients in acceleration and displacement, at different amplitudes of base vibrations, damp-ing and stiffness coefficients. Dependences of average values of transmission coefficients in the investigated frequency range are given. Vibration damping is effective when the maximum suspension travel does not exceed the middle section of the static characteristic. The most effective vibration damping, according to the average value of the acceleration transfer coefficient, is achieved at minimum, and for a single-segment characteristic — zero values of the stiffness coefficient. The presence of extreme segments in the characteristic significantly increases the average values of the accelera-tion and displacement transfer coefficients of the suspension. Seat vibration protection systems in real conditions should have a limitation of suspension displacement for ergonomic reasons. The values of the stiffness coefficients of the extreme parts of the static force response, according to the criterion of minimizing the average value of the acceleration transfer coefficient, should be minimized. To substantiate the optimal values of the stiffness coefficients of the extreme sections of the characteristic and viscous friction coefficients, it is advisable to conduct additional studies under step and stochastic impacts.